Membangun Generasi Muda Desa Melalui Pemberdayaan Berbasis Edukasi Lokal - Ryanto Jaten Pratama Petrus; Prayuda Farhan Prasetyanto; Civu Constant Corputty; Erdianus Julianto Bere; Fransisko Rivaldo; Laura Levita; Sara Prihatin; Maura Avilnia Lawerisa; Richo Forland; Oktavianus Egi; Edi Burga Firmansyah; Pidelis Barakat Pagau; Patricia Della; Ekawati; Merkorius Giber; Habel Williem Bako; Gasver Kristian Andreas; Perdianus; Yopy Susanti; Yefta (LPPM Universitas Panca Bhakti, 2026)
This community service activity was motivated by the low level of awareness of character education and basic literacy among rural youth. The program aims to empower the community of Sungai Belidak Village through an educational approach that focuses on children and adolescents as future agents of development. The implementation methods included anti-bullying socialization and supplementary tutoring in basic subjects. The activities were carried out using a participatory approach involving students, parents, teachers, and village officials. The results indicate a significant improvement in participants’ understanding of bullying issues as well as an enhancement of students’ academic abilities. This program contributes to the development of an inclusive and sustainable village education ecosystem and strengthens the role of young generations in asset-based local development.